BUILDING DEMOCRACY FROM THE VILLAGE: A STUDY OF THE POLITICAL PARTICIPATION OF THE SEI SERDANG COMMUNITY - Adilla; M. Nazaruddin; Suadi; Fauzi (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2025)
Pilkades is one of the crucial issues that will determine the future of a village, including in this case the village of Sei Serdang. In this study, the authors wanted to find out what forms of political participation were carried out by the community in village head elections in Sei Serdang Village and what was the background for community political participation to win the same candidate for 3 consecutive periods. The research method used in this research is a qualitative research method using data collection methods in the form of unstructured interviews with informants from Sei Serdang village residents. The results of the research that has been carried out show that the form of political participation carried out during the pilkades in the Sei Serdang village area was carried out in two forms, both in terms of conventional and non-conventional forms of political participation. The background is related to the victory of the same candidate for three times related to how power and intimidation were carried out by the village head of candidate number 1 and also some of the residents who helped him.